Dietary Inflammatory Potential Is Associated With Sarcopenia Among Chronic Kidney Disease Population - Huang, Ying; Zeng, Mengru; Zhang, Lei; Shi, Jingzheng; Yang, Yuan; Liu, Fuyou; Sun, Lin; Xiao, Li (Frontiers in Nutrition, 2022)
Background Sarcopenia, characterized by impaired muscle mass and function, is a common complication and the main reason for bad life quality and high mortality in chronic kidney disease (CKD). Limiting systemic inflammation is a potable intervention for sarcopenia. Dietary inflammatory potential can influence systemic inflammation. However, research about the association between dietary inflammatory potential and sarcopenia in CKD is limited. Aim To investigate the association between dietary inflammatory potential and sarcopenia in the CKD population. Methods We conducted a cross-section study based on the public database of the National Health and Nutrition Examination Survey (NHANES). In total, 2,569 adult CKD participants who had complete data for dietary inflammatory potential and sarcopenia were included. The dietary inflammatory potential was calculated by the dietary inflammation index (DII) score based on dietary recall interviews. We assessed sarcopenia via low skeletal muscle mass measured by dual-energy X-ray absorptiometry. Smooth curve fitting and a generalized linear mixed model were used to evaluate the relationship between DII and sarcopenia. Moreover, subgroup and sensitivity analyses were performed. Results The overall prevalence of sarcopenia among patients with CKD is 19.11%. Smooth curve fitting results displayed that the DII score is near-linear positively associated with sarcopenia. Logistic regression confirmed sarcopenia is independently related to DII scores (odds ratio [OR], 1.17; 95% CI, 1.06–1.29). Subgroup analyses revealed relatively stronger associations between DII and sarcopenia among patients with CKD with other sarcopenia risk factors, such as hypoalbuminemia, low energy intake, low protein intake, and comorbidities. Conclusion The dietary inflammatory potential is independently related to sarcopenia among patients with CKD. Anti-inflammatory diet patterns may be a protective intervention for CKD-associated sarcopenia.